Effect of Entrepreneurial Education in Universities of Education for Sustainable Development and Poverty Eradication in Africa: A Panacea of University Administrators - Serifat, Odumade Akorede (NIU Journal of Social Sciences; Vol 4 No 4 (2018): KIU Journal of Social Sciences, Vol. 4 No. 4, December 2018, 2019)
This study investigated the effect of entrepreneurial education in universities of education for sustainable development and poverty eradication. Two statements of hypotheses were formulated and tested at 0.05 level of significance. A descriptive survey research design was adopted while two hundred and fifty (250) respondents were selected through a purposive random sampling technique among the 300 level students in each of the five (5) Colleges in Tai Solarin University of Education, Ijagun. The data collected were analyzed using the Pearson Product Moment Correlation. The results revealed that there were positive correlations among the variables of the study. The moderate correlation coefficient (r = .258; df = 68; p = .031) indicates that entrepreneurship education has positive relationship with sustainable development.         Based on the findings, it was recommended among others that; government should ensure that schools are equipped with necessary infrastructural and instructional facilities that will make the teaching and learning of entrepreneurship education very effective. Keywords: Entrepreneurial Education, Universities of Education, Sustainable Development, Poverty Eradication, University Administrators